An investigation of the internationalisation of Malay firms in Malaysia - Mahajar, Abdul Jumaat; Md Hussain, Muhammad Nasri (Universiti Utara Malaysia, 2000)
This paper explores the impact of Qualitative and Quantitative Analyses Methods on the Internationalisation of Malay Firms in Malaysia. The study was conducted in 11 states and Federal Territory in West Malaysia between 1997-2000. In the quantitative analysis method that was adopted, the data gathered was obtained from 166 firms and in the qualitative analyses method, 48 firms were interviewed at the Director and Managerial level of small, medium and large firms. Both methods have their own strengths and weaknesses. The results using a quantitative approach showed that there are 15 barriers faced by Malay firms distracting them from engaging in international business, and the qualitative methods showed that 16 barriers. Having reviewed the two methods of analysis, it was felt that both quantitative and qualitative methods were appropriate for this study.